Body composition measurement in highly trained male athletes. A comparison of three methods - de Lorenzo, A.; Bertini, I.; Iacopino, L.; Pagliato, E.; Testolin, C.; Testolin, G. (The Journal of Sports Medicine and Physical Fitness, 2000)
The purpose of the present study was to evaluate the differences in the body composition estimate of highly trained male athletes by three different methods: dual-energy X-ray absorptiometry (DXA), bioelectrical impedance analysis (BIA) and skinfold thickness measurement (SFT). METHODS: The study occurred during a non-intensive training period. The measurements were performed at the Human Physiology laboratory. Participants: forty-three male athletes (19 waterpolo, 9 judo, 15 karate) who exercised regularly at least three hours per day, six days per week. Measurements: DXA, BIA and SFT measurements of percentage fat mass (%FM) and the amount of fat-free mass (FFM) were performed. Statistical analyses: the different %FM estimates by the three methods were compared using a one-way ANOVA, with posthoc Bonferroni test when values were significantly different. The same test was used to compare FFM values. The coefficient of variation (CV%=100xSD/mean) was calculated for each methods. Methodological differences among the various methods were analysed with the method of Bland-Altman. RESULTS: ANOVA test showed significant differences among the three methods. In particular, DXA significantly (p<0.001) overestimated %FM (12.4+/-4.1%) and underestimate FFM (67.0+/-6.9 kg) respect to SFT (7.8+/-0.9 % and 71.0+/-8.2 kg) and BIA (9.9+/-1.4% and 69.4+/-7.9 kg). Also Bland-Altman comparison among the estimates indicated wide differences between methods. CONCLUSIONS: DXA provides different body composition estimates than those derived from skinfold thickness measurement and BIA, so that the methods should not be used interchangeably.